Implementasi Model Latihan Core Stabilization dan Schroth Method dalam Mengatasi Back Pain pada Remaja dengan Skoliosis - Zein, Renni Hidayati; Ismaningsih, Ismaningsih; Muawanah, Siti; Valzon, May; Sartika, Wiwi (Universitas Baiturrahim, 2025)
Posture is good body posture for inactive and active muscles. Improper body posture habits, such as carrying a heavy bag on one shoulder, result in the shoulders becoming higher on the other side, causing weakness in the trunk muscles which triggers the risk of scoliosis. Scoliosis is a spinal deformity characterized by lateral curvature with or without spinal rotation. Scoliosis can be functional scoliosis which can be corrected while structural scoliosis tends to persist. Approximately 15-20% of cases of scoliosis have an unknown initial cause and 80% of cases of structural scoliosis have an idiopathic etiology and are usually found in children or adolescents. The method used is a question and answer lecture and shows the core stabilization training model and the Schroth method. Before being given education, students' level of knowledge regarding scoliosis is first assessed, then measurements are taken with a scoliometer to see the degree of scoliosis. The second stage is the delivery of material about exercise models for scoliosis. As well as practicing the core stabilization model and the Schroth method. The third stage is a posttest to measure students' knowledge after being given education and practicing exercises. This community service is carried out at MA Muallimin Muhammadiyah Bangkinang. with 35 respondents. The results of community service activities showed an increase in knowledge before being given education on average in the sufficient category (score 65-70) as many as 14 people (40%) and after being given education there was an increase in knowledge on average ≥ 75 or good knowledge as many as 28 people (80 %), students can also practice exercises to improve posture and low back pain caused by scoliosis, this exercise model can be done independently, easily, anytime, anywhere without any side effects or costs.